Strategi Marketing Bank BTN Pada Produk KPR Ditinjau Dari Analisa SWOT & Dalam Upaya Meningkatkan Jumlah Minat Nasabah Di BTN KCP Setia Budi - Marpaung, Fenny Krisna; Latif , Abdul; Virginia, Stephanie; Surbakti , Floren Natalia br. (CV. ITTC INDONESIA, 2024)
This study is targeted at analyzing Bank BTN's marketing strategy for KPR (Home Ownership Credit) products using SWOT analysis and evaluating efforts to increase the number of customer interest in BTN KCP SETIA BUDI. This study takes a qualitative descriptive approach to illustrate the strengths, weaknesses, opportunities and threats faced by Bank BTN's KPR products. The information was compiled from in-depth interviews with management and customers, as well as relevant literature studies.